The Influence of Role Plays and Learning Motivation Towards The First Year Room Division Students Speaking Ability at Tourism Polytechnic of Palembang - Indah Wati; Mochammad Rian Ahdian Morena (Jurnal sosial dan sains, 2024)
Speaking ability is an important skill that must be possessed by students, especially in the field of tourism. This study aims to explore the effect of role play and learning motivation on the speaking ability of first-year students of the Rooms Division at Palembang Tourism Polytechnic. This research method used a factorial design with a population of first-year students of the Hospitality Department. The research sample consisted of 32 participants, consisting of 16 people in the Experiment Group and 16 people in the Control Group. Data were collected through questionnaires and two measurement instruments, then analyzed using Two-Way Analysis of Variance. The results showed that there was a significant effect of role play on students' speaking ability, both those with high and low learning motivation. In addition, conventional teaching techniques also had a significant effect on students' speaking ability, depending on their level of learning motivation. The use of role play proved to be more effective than the conventional teaching technique in improving students' speaking ability. This finding shows that there is an interaction between role play and learning motivation that affects students' speaking ability. Therefore, this finding emphasizes the importance of applying innovative methods and high motivation in the learning process to improve students' speaking ability.  The implications of this study suggest that educators prioritize interactive and motivational teaching strategies to improve speaking skills, which are crucial for career readiness in the tourism industry. In addition, role play can be a key component in the curriculum that aims to improve communication skills at various levels of student motivation.